THE PROCESS OF POLYANILINE FORMATION WITH POLYACID - D.A. Karimova; L.M. Usmonova (Western European Studies, 2025)
Polyanilines and interpolymer complexes based on them can be synthesized both by chemical methods and through electrochemical polymerization of aniline in a mother liquor on the electrodes of an electrochemical cell [1,2]. Electrically conductive interpolymer complexes of polyanilines with polyacids obtained by electrochemical methods possess significant physicochemical properties compared to chemically synthesized compounds [3,4]. These include homogeneity of samples, strong adhesion, high electrical conductivity, chemical stability, etc. However, despite numerous research studies in the field of synthesis of polyanilines and interpolymer complexes with polyacids, a unified theory of the polymerization mechanism has not yet been fully elucidated
Keywords: interpolymer; complexes; numerous